Live Confocal Imaging as a Novel Tool to Assess Liver Quality: Insights From a Murine Model. Issue 12 (December 2020) - Cardini, Benno; Fodor, Margot; Hermann, Martin; Wieser, Verena; Hautz, Theresa; Mellitzer, Vanessa; Schwelberger, Hubert; Resch, Thomas; Weißenbacher, Annemarie; Margreiter, Christian; Zelger, Bettina; Tilg, Herbert; et al.
Abstract : Background: In an experimental murine liver clamping model, we aimed to investigate the efficacy of real-time confocal microscopy (RCM) in assessing viability of steatotic livers in comparison to standard assessment tools, including histopathological evaluation. Methods: C57Bl/6 mice were subjected to a methionine-choline-deficient diet causing nonalcoholic fatty liver disease or to Lieber DeCarli diet causing ethanol-induced liver injury. Untreated animals served as controls. Liver biopsies were analyzed following challenge with 45 min of warm ischemia time and either 4 h of reperfusion or 24 h of cold storage. Organ quality assessment was performed at defined time points by RCM, histological staining, measurement of serum alanine aminotransferase activity, and expression analyses of proinflammatory cytokines. Additionally, survival analysis was performed. Results: Cold as well as warm ischemia time resulted in a significant decrease in cell viability when compared with naive livers as well as nonischemic-challenged steatotic livers ( P < 0.05) as assessed by RCM. Furthermore, RCM revealed the actual cellular damage at early time points, while established methods including H&E-staining and serum transaminase profile failed. Conclusions: In a translational attempt, we demonstrate that RCM is a suitable diagnostic tool to obtain information about functional damage of the liver apart from standard approaches. Abstract : Supplemental Digital Content is available in the text.